Evaluation of Reverse Logistics in the Paint Distribution Process Using The Pareto Method and Cuase-and-effect Analysis - Purwoko, Harry; Hutauruk, Paul S.; Anisyah, Diah; Isnaini, Firna Destiayu (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2024)
PT XYZ is a renowned company engaged in the distribution of paint products, catering to the regions of East Jakarta, North Jakarta, and Central Jakarta. PT XYZ experienced many returning paint problems from the outlets due to damage that impacted customer satisfaction and both sides’ losses. Diligent researchers meticulously collected a comprehensive set of return data from January to June 2023 to ascertain the extent of paint damage and identify the underlying causes. The study aims to assess the extent of paint damage resulting from various factors to minimise future damage. This research uses qualitative research methods with quality testing tools, namely the Pareto concept, the analysis of the 5 whys, cause-and-effect analysis, and focus group discussion (FGD). The Pareto method revealed that the highest return value was 241 cans of wall paint from customers for Rp. 46,626,800. The biggest common reason for paint returns was paint packaging leakage, which accounted for 59.3%. Based on this research, the factors that can reduce paint packaging leaks are better handling practices and procedures.